The complete chloroplast genome of Antiaris toxicaria, a medicinal and extremely toxic species. Issue 2 (3rd July 2018) - Zhang, Lushui; Yang, Xiaoyue; Mao, Xingxing; Wang, Zefu
Abstract: Antiaris toxicaria ( Antiaris, Moraceae) is a medicinal and extremely toxic species. To facilitate species identification and provide genetic information, we determined the complete chloroplast genome of A. toxicaria using the Illumina platform. The genome was 161, 412 bp in length, comprising a large single-copy region (LSC) of 89, 883 bp, a small single-copy region (SSC) of 20, 375 bp, and a pair of inverted repeats (IRs) of 25, 577 bp each. The genome contained 130 encoded genes in total, including 85 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. The overall GC content of the A. toxicaria chloroplast genome is 35.87%. The phylogenetic analysis revealed A. toxicaria was closely related to the genus Ficus within the family Moraceae.